Evaluation of aquifer parameters from drawdown data in borewells - CHITHRA G; Gentle Jose; Manju K. Moni; Er. Levan K. V (Guide) (Tavanur 2004 Kelappaji College of Agricultural Engineering and Technology)
Evaluation of aquifer parameters from drawdown data in borewells
Evaluation of aquifer parameters from drawdown data in borewells